2005
DOI: 10.1161/01.res.0000151333.56089.66
|View full text |Cite
|
Sign up to set email alerts
|

Small Artery Remodeling Depends on Tissue-Type Transglutaminase

Abstract: Abstract-Remodeling of small arteries is essential in the long-term regulation of blood pressure and blood flow to specific organs or tissues. A large part of the change in vessel diameter may occur through non-growth-related reorganization of vessel wall components. The hypothesis was tested that tissue-type transglutaminase (tTG), a cross-linking enzyme, contributes to the inward remodeling of small arteries. The in vivo inward remodeling of rat mesenteric arteries, induced by low blood flow, was attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(195 citation statements)
references
References 37 publications
11
183
0
1
Order By: Relevance
“…Inhibitors of TG2 block inward remodeling that was induced by endothelin-1. Enhanced expression of endogenous TG2 or the application of exogenous TG2 increases inward remodeling in several animal models (94). In a porcine model of renal artery stenosis, simvastatin inhibited the inward remodeling of the intrarenal microvasculature, partly by decreasing the upregulation of TG2 expression in the ischemic kidney (95).…”
Section: Transglutaminases and Arterial Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of TG2 block inward remodeling that was induced by endothelin-1. Enhanced expression of endogenous TG2 or the application of exogenous TG2 increases inward remodeling in several animal models (94). In a porcine model of renal artery stenosis, simvastatin inhibited the inward remodeling of the intrarenal microvasculature, partly by decreasing the upregulation of TG2 expression in the ischemic kidney (95).…”
Section: Transglutaminases and Arterial Remodelingmentioning
confidence: 99%
“…Interestingly, the activity of TG2 appears to be regulated, in part, by the application of pressure to the arterial wall (94). Both TG2 and FXIII transglutaminase activities are also regulated by nitric oxide.…”
Section: Transglutaminases and Arterial Remodelingmentioning
confidence: 99%
“…20,22,23,32,33,37 In addition to being a model that mimics the remodeling that occurs in hypoperfused tissues, LF remodeling has been shown to be equivalent to the eutrophic inward remodeling observed in several types of hypertension, such as endothelin-1-dependent hypertension and L-NAME-induced hypertension. 10 The main finding of this study is that the diameter reduction because of a decrease in blood flow in RAs was prevented by perindopril and candesartan, but not by hydralazine, suggesting selective involvement of angiotensin II and of its AT1R. The AT2R was not involved in this remodeling (see Supplementary information).…”
Section: Discussionmentioning
confidence: 61%
“…This contraction is then stabilized by the activation of tissuetransglutaminases. 10 Using mice lacking tissue angiotensin I-converting enzyme, Hilgers et al 11 showed that this enzyme has a major role in hyperplasic inward remodeling of the carotid artery after blood flow cessation. In mesenteric RAs, we have previously shown that acute stimulation of the endothelium by flow (shear stress) induces vasodilation, which is modulated by the local production of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms which may modulate resistance arterial eutrophic remodelling is thus important, but these remain poorly understood. Prolonged vasoconstriction appears important, which, in itself may modulate re-organisation via the activities of cross-linking enzymes such as tissue-type transglutaminase and/ or integrins (Bakker et al, 2002(Bakker et al, , 2005Heerkens et al, 2006). It has been proposed that initial eutrophic remodelling may be an energetically favourable adaptive mechanism to normalise wall stress to maintain adequate blood flow, whilst a growth response, which may be observed in advanced or secondary hypertension, is related to a greater adverse prognosis (Izzard et al, 2006;Heagerty et al, 2010).…”
Section: Resistance Artery Structure and Hypertensionmentioning
confidence: 99%